Puntius viridis (Cypriniformes, Cyprinidae), a new fish species from Kerala, India - Plamoottil, Mathews; Abraham, Nelson P. (Journal of Research in Biology, 2014)
Taxonomic analysis of eight specimens of a cyprinid fish collected from Manimala River, Kerala, India revealed that they present several morphological differences from their congeners. The new species, Puntius viridis, is diagnosed by a combination of the following characters: eyes clearly visible from below ventral side; head depth lesser; one row of prominent elongated black spots on the middle of dorsal fin; a black band formed of dark spots present outer to operculum. 25-26 lateral line scales; 4½- 5½ scales between lateral line and dorsal fin; moderate scales on the breast region